POTENSI PENGGUNAAN EKSTRAK DAUN SAGA (Abrus precatorius) sebagai ANTI BAKTERI Aeromonas hydrophila secara In Vitro - Rahmalia Eka Kenitasari; Arief Prajitno; Arning Wilujeng; Genesia Gerrine (Postgraduate, University of Mataram, 2023)
Many diseases are caused by bacterial pathogens, for example, Aeromonas hydrophila. One alternative that can be done to overcome this problem is to use saga leaves (Abrus precatorius) which have bioactive ingredients as antibacterial ingredients. The aims of this study were to determine the antibacterial activity of saga (A. precatorius) leaf extract, to study the character and structure of bacteria inhibited by saga (A. precatorius) leaf extract and to study the bioactive components contained in saga (A. precatorius) leaf extract. The results of the disc test showed that the average inhibition zone was 14,29 mm while the MIC test results showed that at the dose 1 mg/L capable of inhibiting bacterial growth (bacteriostatic) and dose 10 mg/L It has been able to kill bacteria (bactericidal). Crude extract of saga leaf extract (A. precatorius) affects the character and structure of A. hydrophila bacteria by damaging the cell walls and cell membranes of bacteria. The results of Infrared Spectrophotometry analysis of saga (A. precatorius) leaf extract and Ultra Violet Spectrophotometry analysis with 96% absorption ethanol were suspected to contain flavonoid compounds